1957
DOI: 10.1085/jgp.41.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Uphill Transport Induced by Counterflow

Abstract: ABSTRACT1. In a membrane transport system containing a mobile carrier with affinities for two substrates a concentration gradient with respect to one of the substrates under certain conditions is able to induce an "uphill" transport (against the concentration gradient) of the other.2. In a kinetic treatment quantitative conditions for such a "flow-induced uphill transport" and some of its characteristics are derived.3. Experimentally the uphill transport of labelled glucose induced by a concentration gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(81 citation statements)
references
References 7 publications
(8 reference statements)
2
79
0
Order By: Relevance
“…This was first observed in erythrocytes as uphill hexose counterflow (other terms include countertransport acceleration and trans-stimulation transport). 111,112 In these experiments, hexose was detected flowing apparently against its concentration gradient from the cis side into the trans side of the membrane where hexose is also present, and vice versa. Rosenberg and Wilbrandt argued that the phenomenon was due to two different transport systems present in the red cell, which Naftalin and Holman referred to as a two binding site carrier.…”
Section: Mechanism Of Trans-accelerationmentioning
confidence: 80%
“…This was first observed in erythrocytes as uphill hexose counterflow (other terms include countertransport acceleration and trans-stimulation transport). 111,112 In these experiments, hexose was detected flowing apparently against its concentration gradient from the cis side into the trans side of the membrane where hexose is also present, and vice versa. Rosenberg and Wilbrandt argued that the phenomenon was due to two different transport systems present in the red cell, which Naftalin and Holman referred to as a two binding site carrier.…”
Section: Mechanism Of Trans-accelerationmentioning
confidence: 80%
“…Without any molecular knowledge of the carrier proteins themselves, descriptions were made of driving forces for uphill transport such as electrochemical gradients of ions (Heinz 1972;Semenza and Kinne 1985;Alvarado and Van Os 1986), counter-or antiporttransport (Rosenberg and Wilbrandt 1957;Heinz 1978), membrane potential (Ward 1970;Athayde and Ivory 1985) or direct energy transmission due to ATP-cleavage (Caldwell 1956(Caldwell , 1960Keynes 1961;Carafoli and Scarpa 1982). Although it was suggested very early (Sperber 1959), it was later shown that drug excretion and absorption is strongly dominated by membrane carrier proteins, i.e.…”
Section: Functional Indications Of Drug Transportersmentioning
confidence: 99%
“…However, there are some important differences in the way that the squid axon and the human red cell transport sugars. In the human red cell, both glucose uptake and exit are increased when glucose is present at the opposite, trans-side of the membrane P. F. BAKER AND A. CARRUTHERS (Rosenberg & Wilbrandt, 1957;Miller, 1968). In the squid axon, sugar exit is reduced by external sugar and uptake is unaffected by axoplasmic sugar.…”
Section: Characteristics Of 3-0-methylglucose Transport In Squid Axonsmentioning
confidence: 99%